Evaluation of The Use of Color and Identity Formation in Educational Spaces: The Case of the Eastern Mediterranean University Campus-North Cyprus - Azizi, Amirhossein (Eastern Mediterranean University, 2025)
A basic component of architectural and interior architecture, color shapes spatial perception, cognitive ability, and emotional reactions. Though important, its use in learning environments is still mostly arbitrary and usually devoid of a method grounded on empirical data. With an especially eye on its effects on spatial identity, navigation, and user experience, this study looks at how color shapes educational environments. The primary research question is: Can a methodical approach to employing color improve the quality of spaces in various educational environments? The study seeks to close the gap between color theory and its pragmatic implementation in educational institutions. To investigate this, the study looks at the relationship between color and spatial identity and investigates whether the properties of color could help shape a methodical approach to the design of learning environments. Using a mixed-method approach—that which combines qualitative and quantitative techniques—this study uses While field observations, organized inventory tables, and graphic documentation add empirical evidence, a thorough literature review creates a theoretical basis. The distribution and impact of color in educational settings are evaluated using quantitative studies. The case study is on Eastern Mediterranean University (EMU), where particular instructional environments are examined to assess present color schemes and suggest changes. The study admits certain limits that greatly affect color visibility: cultural differences in color perception and the absence of lighting influences. Moreover, the study is limited to faculty buildings on the university campus, therefore eliminating auxiliary areas including sports facilities and student service centers. The results show that a well-organized technique for color application in educational environments improves spatial awareness, cognitive function, and emotional well being. Based on the purpose of each place, the study advises different colors should be used strategically: cool tones like blue and green in schools to promote focus, warm hues in social areas to encourage engagement, and neutral colors in transitional zones to help orientation. The study concludes that adding an evidence-based color strategy will help to raise the general functionality and quality of learning surroundings. This study offers a disciplined framework for the use of color, therefore supporting the larger debate on design in education. It provides insightful analysis for builders, teachers, and legislators trying to maximize learning settings with well-chosen colors. Future studies should take lighting and color interaction into account to improve spatial cognition in learning environments even more. Keywords: Color, Educational Spaces, Space Identity, Cognitive Effects of Color, Campus Design.

Mimari ve iç mimari temel bir bileşeni olan renk, mekânsal algıyı, bilişsel yetileri ve duygusal tepkileri şekillendirir. Ancak, öğrenme ortamlarında kullanımı hâlâ büyük ölçüde rastlantısaldır ve çoğunlukla ampirik verilere dayalı sistematik bir yöntemden yoksundur. Özellikle mekânsal kimlik, yönlendirme ve kullanıcı deneyimi üzerindeki etkilerine odaklanan bu çalışma, rengin eğitim ortamlarını nasıl biçimlendirdiğini araştırmaktadır. Bu bağlamda, temel araştırma sorusu şudur: Renk kullanımına yönelik sistematik bir yaklaşım, farklı eğitim ortamlarındaki mekân kalitesini artırabilir mi? Çalışma, renk teorisi ile eğitim kurumlarındaki uygulamalı kullanımı arasındaki boşluğu kapatmayı amaçlamaktadır. Bu doğrultuda, renk ile mekânsal kimlik arasındaki ilişki incelenmekte ve rengin belirli niteliklerinin, öğrenme ortamlarının tasarımında sistematik bir yaklaşımı şekillendirmeye yardımcı olup olamayacağı araştırılmaktadır. Nitel ve nicel yöntemleri bir araya getiren karma yöntem kullanılarak yürütülen bu çalışmada; saha gözlemleri, düzenlenmiş envanter tabloları ve grafik dokümantasyon gibi ampirik kanıtlar sunulurken, kapsamlı bir literatür taraması kuramsal bir temel oluşturmaktadır. Eğitim ortamlarında rengin dağılımı ve etkisi, nicel analizler ile değerlendirilmektedir. Doğu Akdeniz Üniversitesi (DAÜ) vaka çalışması olarak ele alınmış, belirli eğitim mekânları incelenerek mevcut renk şemaları değerlendirilmiş ve iyileştirme önerileri sunulmuştur. Çalışma, renk algısında kültürel farklılıklar ve aydınlatma etkilerinin göz ardı edilmesi gibi renk görünürlüğünü önemli ölçüde etkileyen bazı sınırlılıkları kabul etmektedir. Ayrıca araştırma, üniversite kampüsündeki fakülte binalarıyla sınırlı tutulmuş olup spor tesisleri ve öğrenci hizmet merkezleri gibi yardımcı alanlar kapsam dışı bırakılmıştır. Elde edilen bulgular, eğitim ortamlarında renk uygulamasına yönelik iyi organize edilmiş bir yöntemin mekânsal farkındalığı, bilişsel işlevleri ve duygusal iyi oluşu artırdığını göstermektedir. Çalışma, her mekânın işlevine bağlı olarak farklı renklerin stratejik olarak kullanılmasını önermektedir: Dikkati artırmak için okullarda mavi ve yeşil gibi soğuk tonlar, etkileşimi teşvik etmek için sosyal alanlarda sıcak renkler ve yön bulmayı kolaylaştırmak için geçiş bölgelerinde nötr renkler tercih edilmelidir. Sonuç olarak, ampirik verilere dayalı bir renk stratejisinin eğitim ortamlarının genel işlevselliğini ve kalitesini yükselteceği vurgulanmaktadır. Bu çalışma, renk kullanımına yönelik disiplinli bir çerçeve sunarak eğitim tasarımı konusundaki daha geniş tartışmalara katkı sağlamaktadır. Mimarlar, eğitimciler ve politika yapıcılar için öğrenme ortamlarını en iyi şekilde düzenlemek adına değerli bir analiz sunmaktadır. Gelecek araştırmalar, mekânsal bilişi daha da geliştirmek için aydınlatma ile renk etkileşimini ele almalıdır. Anahtar Kelimeler: Renk, Eğitim Mekânları, Mekânsal Kimlik, Rengin Bilişsel Etkileri, Kampüs Tasarımı.
İç Mimarlık - Yüksek Lisans Tezi. Lisansüstü Eğitim, Öğretim ve Araştırma Enstitüsü. Tez (Yüksek Lisans) - Doğu Akdeniz Üniversitesi, Mimarlık Fakültesi, İç Mimarlık Bölümü, 2025. Tez Danışmanı: Asst. Doç. Dr. Kamil Güley.
Keywords: Architecture; Interior; Color in interior decoration; Educational facilities--Design and construction; Educational buildings--Psychological aspects; Space perception; Universities and colleges--Cyprus; Northern; Campus planning--Cyprus; Environmental psychology; Color in architecture; Color; Educational Spaces; Space Identity; Cognitive Effects of Color; Campus Design